COGNITIVE THERAPY AS A TOOL TO REDUCE THE RISK OF BURNOUT IN NURSES (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Burnout syndrome is one of the most pressing professional problems among nurses caused by a complex of factors, including high emotional stress, permanent stress, and the specifics of cognitive processing of professional situations. The research objective was to identify the factors contributing to the development of emotional burnout in nurses and to substantiate the role of cognitive therapy as a preventive measure. The research methodology included a logical and psychological analysis of scientific literature, conducting a sociological survey, statistical processing of the data obtained and the use of elements of cognitive behavioral support. 36 nurses from various medical institutions participated in the survey. The MBI scale modified by N.E. Vodopyanova was used to quantify the level of emotional burnout. The results demonstrated a high level of emotional exhaustion, the presence of sleep disorders, psychosomatic complaints, and the prevalence of maladaptive forms of stress management. Based on the data obtained, it is concluded that it is advisable to integrate cognitive-oriented preventive programs into the system of professional support for nursing staff.
Keywords: Burnout syndrome, nurses, occupational stress, cognitive therapy, Maslach Burnout Inventory, prevention.